Pengaruh Model Problem-Based Learning terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas V - Rahmawati, Pritha; Irawati, Riana; Isrok’atun, Isrok’atun (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is motivated by the low mathematical conceptual understanding of fifth-grade students regarding data collection and presentation. The conventional, teacher-centered learning process is considered ineffective in fostering deep understanding. This study aims to determine the difference in the effect of the Problem-Based Learning (PBL) model and conventional learning on students' conceptual understanding. This study employed an experimental method with a non-equivalent control group design. The population comprised fifth-grade students in Sumedang Regency. Through purposive sampling, SDN Sindang II (n=31) was selected as the experimental class, and SDN Hariang (n=34) as the control class. The instruments used were tests and observations. Data analysis for the conceptual understanding test was conducted using inferential statistics to draw conclusions. The results showed that the experimental class's average score increased from 54 (pretest) to 67 (posttest) with an average N-Gain of 0.28. Meanwhile, the conventional learning class obtained an average pretest score of 62, increasing to 66 in the posttest, with an average N-Gain of 0.07. It is concluded that there is a significant difference in influence between the Problem-Based Learning model and conventional learning on students' conceptual understanding